Controlled synthesis of zigzagged and straight Ga-doped ZnO nanowires in hot-walled pulsed laser deposition - Song, Yong-Won; Lee, Sanggyu; Lee, Sang Yeol (ELSEVIER SCIENCE BV, 2008)
We synthesize zigzagged and straight Ga-doped ZnO nanowires (NWs) carefully controlling the doping-induced stress in the stacked structures of the individual NWs. The analysis of the zigzag shaping is approached with tracking the local stress migration in the NW crystals. Self-designed hot-walled pulsed laser deposition is employed to guarantee the wide window for the condition of successful NW formation. The density and kinetic energy of the laser-ablated particles from a target are optimized by tuning the laser operation condition, and the activation energy for switching the growing crystal directions is adjusted by controlling the synthesis temperature and the catalyst dimension to achieve the zigzagged morphology. The doping into the NWs is verified with photoluminescence measurement at low and room temperatures. Resultant zigzagged ZnO NWs successfully prepared with diversified Ga-doping concentration are analyzed, and compared with each other in terms of the morphology and growth kinetics. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: ARRAYS; TARGET